Correlation Between Personality Disorder and Neuroplasticity: Can Deprivation Lead to Advantage and Resourcefulness? - Thomson, Wendy (British Journal of Healthcare and Medical Research, 2024)
This paper explores the new hypothesis that neuroplasticity is associated with personality disorder. Specifically, it provides a possible explanation for why some severely deprived individuals develop the ability to positively adapt and adjust. It discusses a case in which [In the Methodology] Often uneducated, they had survived through their own resourcefulness. For example, those of them who were substance-addicted became so because they were self-medicating to combat their health challenges, which, in most cases, were caused by their deprivation. [In the Discussion] At puberty, when there is an explosion of neurons, there is a parallel need for circumstances that both maximise and facilitate neural connections. Privileged children and teens may be deprived of this due to societal and educational constraints, such as lack of freedom to explore, to be innovative and to be open to many different experiences. Thus, they will not benefit in terms of neural connectivity—in fact, they could be in deficit. In this study, the brains of children living so-called ‘deprived lives’, free from normal constraints, such as not complying with social norms for whatever reason, seemed to have developed the ability to make neural connections, which increased their overall potential to cope in the future competitive world. Therefore, deprivation, although negative, appeared to be an asset in these young ‘personality-disordered’ patients.